Pendampingan Usaha Kecil, Mikro, dan Menengah Kelurahan Kedung Baruk Melalui Media Sosial Instagram sebagai Upaya dalam Pengoptimalan Promosi Digital - Fadilla Ryandini; Zawawi Zawawi (jurnal ABDIMAS Indonesia, 2023)
Abstract: The rapid development of technology and digitalization currently has an impact on all aspects of life. Current technological developments affect world marketing which is shifting into the digitalization era. This creates a new and easy way for businesses to learn about consumer behavior, brands and services that match the wants and needs of today's customers. The aim of this program is to help MSMEs in the Kedung Baruk Village to maximize social media as a marketing tool. For this program the author uses a special assistance method in implementing the planned program. This assistance program specifically selects MSMEs in the Kedung Baruk Village.